Heparan sulfate proteoglycans and heparin regulate melanoma cell functions - Nikitovic, D.; Mytilinaiou, M.; Berdiaki, Ai; Karamanos, N.K.; Tzanakakis, G.N. (Biochimica et biophysica acta, 2014)
The solid melanoma tumor consists of transformed melanoma cells, and the associated stromal cells including fibroblasts, endothelial cells, immune cells, as well as, soluble macro- and micro-molecules of the extracellular matrix (ECM) forming the complex network of the tumor microenvironment. Heparan sulfate proteoglycans (HSPGs) are an important component of the melanoma tumor ECM. Importantly, there appears to be both a quantitative and a qualitative shift in the content of HSPGs, in parallel to the nevi–radial growth phase–vertical growth phase melanoma progression. Moreover, these changes in HSPG expression are correlated to modulations of key melanoma cell functions. This review will critically discuss the roles of HSPGs/heparin in melanoma development and progression. We have correlated HSPGs' expression and distribution with melanoma cell signaling and functions as well as angiogenesis. The current knowledge of HSPGs/heparin biology in melanoma provides a foundation we can utilize in the ongoing search for new approaches in designing anti-tumor therapy. This article is part of a Special Issue entitled Matrix-mediated cell behaviour and properties. •Melanoma is a highly metastatic tumor with fatal complications.•There are distinct quality variations in melanoma ECM.•HSPGs are strongly involved in melanoma cell functions through their fine structure.•HSPGs could be potential therapeutic targets against melanoma progression.